Basic circuit reliability for digital HF ionospheric communications. - Bradley, P.A. (Física de la Tierra, 2000)
Modem radio communication systems require estimates of basic circuit reliability to assess the probability that satisfactory performance will be achieved. Por these, a knowledge is needed of both propagation effects and operational requirements. An intemationally adopted calculation method exists for HE analogue systems based on satisfying defmed signal/noise ratios, but for digital systems attention must additionally be paid to meeting maximum pennilted dispersion criteria. A new method of evaluation to achieve this is introduced as an extension of the procedure for analogne systems. The various inherent assumptions are discussed and the justifocation for the adopted approach is examined.